The Influence of Organizational Support, Career Development, and Organizational Culture On Employee Performance, With Organizational Commitment to Act As a Mediator - Ezat Indra Saputra; M. Farid Wajdi (Nusantara Science and Technology Proceedings, 2023)
In the industrial world, employee performance is a crucial element in determining the success of a business. Extensive research has been conducted to identify factors that influence employee performance, in particular, the general tendency to leave a job. This research aims to explore how perceptions of organizational support, career development, and organizational culture influence employee performance, with organizational commitment as the mediator. This research uses a quantitative descriptive approach by utilizing perceptions of organizational support, career development, and organizational culture as independent variables and employee performance as a dependent variable which is mediated by organizational commitment. The research population was employees of OneCare Wellness Malaysia Company who used the saturation or census method with data collected from 44 employees. An online questionnaire distributed via Google Form facilitated data collection, while multiple linear regression analysis was used to analyze the findings. The results of data processing using SPSS software show that perceptions of organizational support and career development do not have a direct and significant influence on employee performance. It is important to note that not all employees feel the support provided by the company, and some employees may not have the same opportunities for career development. On the other hand, organizational culture has a direct and significant influence on employee performance, organizational commitment successfully mediates the independent variable in the dependent research.